Live-Life cycle assessment of the electric propulsion ship using solar PV - Park, Chybyung; Jeong, Byongug; Zhou, Peilin; Jang, Hayoung; Kim, Seongwan; Jeon, Hyeonmin; Nam, Dong; Rashedi, Ahmad (Applied energy, 2022)
•Lifecycle benefits/harms of solar/electric ships were demystified quantitatively.•Live-Life Cycle Assessment was introduced to overcome the lack of data available.•Environmental performance of solar ships was subject to geographical conditions.•Green electric grids were suggested to contribute to net zero-emission shipping. This paper was born to introduce a novel methodology termed Live-Life Cycle Assessment using a simulation-based data generation technique that can remedy the inherent shortcomings of conventional practices of lifecycle assessment. To demonstrate its excellence, the proposed method was applied to one of the most challenging topics in the marine industry. That was to tackle the fundamental doubt of whether solar-electric propulsion ships could truly be the future energy solution of maritime transports by fulfilling new environmental conventions and goals around the world. The case study began with an existing hybrid short route ferry running on diesel and plug-in battery power. Credible PV systems for the case ship was modelled to produce ship performance data under various operational/environmental circumstances of the coastal zones across 29 countries in the platform of MATLAB/Simulink. As a key functionality of Live-Life Cycle Assessment, the produced data was directly fed, as inputs, into life cycle assessment to avoid conventional practices that heavily rely on outdated data libraries. Results of the case study clearly revealed and quantified the correlations of the performance of PV-battery systems with climate parameters such as temperature and irradiance of subject areas as well as national power production methods. For example, in terms of Global Warming Potential, the case ship with the PV system was estimated to reduce 40,812 kg CO2 eq. per year in Brazil (average temp.: 27.4 ℃, major energy source: hydro). Interestingly, the same vessel was found to achieve greater reductions in India (average temp.: 27.5 ℃, major energy source: coal) or Australia (average temp.: 20.1 ℃, major energy source: coal) where are overly laden with coal-based power plants. Therefore, their reduction levels were estimated at 152,887 kg CO2 eq. per year and 141,517 kg CO2 eq. per year respectively. This paper clearly shows the excellence of the proposed method to demystify/quantify the impacts of parametric variables on the performance of the PV-electric ship. Moreover, it highly suggests the Live-Life Cycle Assessment could be a solution as a new standard to respond to strong demand to obtain general observation of lifecycle benefits/harms of new technologies across all industries, not necessarily limited to the maritime sector.